2010
DOI: 10.21608/jva.2010.44897
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Morphology of the Mystacial Vibrissae in the African Giant Pouched Rat (Cricetomys gambianus, Waterhouse-1840)

Abstract: Anatomy of the mystacial vibrissae in the African giant pouched rat was investigated to establish the role played by these structures in the adaptation of the rodent to its subterranean environment. Gross morphology was based on direct observation of the mystacial vibrissae with the naked eyes, while histology was based on light microscopic examination of the same structure stained with haematoxylin and eosin (H/E), Masson's trichrome (MT) and Masson-Fontana reducing method for melanin. The mystacial vibrissae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
(37 reference statements)
3
11
1
Order By: Relevance
“…Ibe et al (5) observed the presence of plantar digital pads and absence of palmar digital pads in the African giant pouched rat, unlike in the present study. The African giant pouched rat is a subterranean rodent which digs with the claws and uses the plantar pad to push excavated soil away (5). The broader plantar than palmar surface observed in this study may be compensatory for the lack of plantar digital pads.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Ibe et al (5) observed the presence of plantar digital pads and absence of palmar digital pads in the African giant pouched rat, unlike in the present study. The African giant pouched rat is a subterranean rodent which digs with the claws and uses the plantar pad to push excavated soil away (5). The broader plantar than palmar surface observed in this study may be compensatory for the lack of plantar digital pads.…”
Section: Discussioncontrasting
confidence: 94%
“…Paw width was obtained as the greatest radial to ulnar extent of the paw, measured with centimeter rule. The experimental procedures of Ibe et al (5) were adopted for obtaining skin samples from the trunk and limbs for light microscopic examination and for histological preparation of the samples. The slides were stained with hematoxylin and eosin stains.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…For electron microscopy, Karnovsky's fixative (Glutaraldehyde + Paraformaldehyde + Sodium hydroxide in buffer solution) will be more appropriate. On the shrinkage factor of the rodent brain, Ibe et al, (2010), showed that the AGR had negligible shrinkage following 3 days post fixation in 10% formalin. This assumption is adopted by the authors also.…”
Section: Discussionmentioning
confidence: 99%
“…e. Weighing the brain: Brain weight offers great insight into changes that may have occurred in the brain. These changes may vary from sexual dimorphisms (Ibe et al, 2010), to pathological changes (Skullerud, 1985;Mustapha et al, 2014). These weight parameters may be correlated against body parameters such as body (head, trunk and tail) lengths or body weights.…”
Section: Figurementioning
confidence: 99%